Cloud Condensation Nuclei Closure Study Using Airborne Measurements Over the Southern Great Plains. Issue 5 (23rd February 2023) - Kulkarni, Gourihar; Mei, Fan; Shilling, John E.; Wang, Jian; Reveggino, Renato Pinto; Flynn, Connor; Zelenyuk, Alla; Fast, Jerome
Abstract: Airborne measurements of non‐refractory bulk aerosol chemical composition, aerosol size distributions, and cloud condensation nuclei (CCN) were conducted onboard a research aircraft during the Holistic Interactions of Shallow Clouds, Aerosols and Land Ecosystems field campaign in the spring and summer of 2016. A CCN closure study for the entire campaign period was performed where measured CCN concentrations at 0.24% and 0.46% supersaturation were compared with the predicted CCN concentrations calculated using κ ‐Köhler theory, three different assumptions of aerosol mixing state, and various assumptions about hygroscopicity, density, and the insoluble fraction of organic particles. We found that the Closure Ratio (CR), calculated as the ratio of predicted to measured CCN concentrations, was equal to one under two different aerosol mixing state assumptions: (a) all particles are composed of 100% organic particles, and (b) particles are externally mixed and composed of pure sulfates, nitrates, and organic particles assuming hygroscopicity values for organic particles ( κ o r g ${κ }_{org}$ ) between 0.04 and 0.17. The use of internal mixing state assumption often led to overprediction of CCN concentrations but the agreement within ±20% with the measured CCN concentrations was observed under certain closure permutations. A similar agreement, that is, within ±20%, was also observed using permuted parameters concerning density (1 and 1.5 g cm −3 ) and an insoluble fraction (0% and 20%) of organic particles. These findings may provide constraints on κ o r g ${κ }_{org}$ to predict CCN concentrations at a remote continental Southern Great Plains site. Plain Language Summary: A large number of foreign particles suspended in the atmosphere, or atmospheric aerosols, provide centers upon which water‐vapor condensation could occur. The affinity of various atmospheric aerosols for water is a key factor controlling their ability to act as cloud condensation nuclei (CCN), and hence the study of CCN is of prime importance to understanding the formation of clouds—the key components of the Earth's atmosphere. Such hygroscopic behavior of aerosols from a remote continental Southern Great Plains (SGP) geographical region, where airmass arrives from local and long distances is poorly understood. The airborne measurements of these individual mixed aerosols at SGP were performed using a research aircraft. We analyzed the size and number counts and CCN properties of these individual particles using different assumptions of the chemical composition that each particle is made up of. We find that if all the particles are composed of 100% organics, or if the particle population consists of three aerosol types with each type composed of pure organics, sulfates, and nitrates, then one can theoretically calculate CCN numbers within 20% uncertainty under certain thermodynamic conditions. Our conclusions may be useful to model hygroscopicity values of ambient aerosol from the SGP site. Key Points: Aerosol cloud condensation nuclei (CCN) characteristics such as hygroscopicity and closure ratio (CR) for each constant altitude leg of the entire campaign were assessed The CCN CR was calculated under various permutations concerning the hygroscopicity, solubility, and density of organic particles A modest closure using a single component, internal, and external aerosol mixing states at certain permutation parameters can be achieved